Analisis Minat Belajar Penjas Terhadap Kemampuan Dasar Bermain Sepakbola Murid SDI Maccini Sombala Makassar - Fahrizal Fahrizal; Ishak Bachtiar (Phsyical Education Health and Recreation Department of STKIP-YPUP Makassar, 2021)
This study aims to determine the interest in learning physical education, to determine the basic skills of playing football and to determine the relationship between interest in learning physical education and the basic skills of playing football at the Inpres Maccini Sombala Elementary School, Makassar City. The number of samples used in this study were 30 people who were randomly selected from 5th and 6th grade students of SD Inpres Maccini Sombala Makassar City. This type of research is a quantitative descriptive research, which describes the existing information in accordance with the variables studied. Descriptive quantitative research is not to test hypotheses, to describe phenomena that appear in the field. From the results of a simple regression analysis between interest in learning physical education and the basic ability to play football at the Inpres Maccini Sombala Elementary School, Makassar City, the relationship value is r = 0.898 (P = .000 < 0.05), then H0 is rejected and H1 is accepted, meaning there is a significant relationship between interest in learning physical education and the basic ability to play football at the Inpres Maccini Sombala Elementary School Makassar City.